2016
DOI: 10.3791/53927
|View full text |Cite
|
Sign up to set email alerts
|

A Step by Step Protocol for Subretinal Surgery in Rabbits

Abstract: Age related macular degeneration (AMD), retinitis pigmentosa, and other RPE related diseases are the most common causes for irreversible loss of vision in adults in industrially developed countries. RPE transplantation appears to be a promising therapy, as it may replace dysfunctional RPE, restore its function, and thereby vision.Here we describe a method for transplanting a cultured RPE monolayer on a scaffold into the subretinal space (SRS) of rabbits. After vitrectomy xenotransplants were delivered into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…The advancement of OCT technology provided rapid assessment of transplant morphology and placement location in the eye [ 9 , 52 , 197 , 198 ]. The use of OCT imaging to assess changes in the retinal thickness posttransplantation has been established [ 9 , 197 201 ]. The above studies conducted in rat models suggested that OCT is a reliable tool for in vivo screening and evaluation of retinal transplants.…”
Section: Tools and Approaches For In Vivo Assessment Of The Transpmentioning
confidence: 99%
“…The advancement of OCT technology provided rapid assessment of transplant morphology and placement location in the eye [ 9 , 52 , 197 , 198 ]. The use of OCT imaging to assess changes in the retinal thickness posttransplantation has been established [ 9 , 197 201 ]. The above studies conducted in rat models suggested that OCT is a reliable tool for in vivo screening and evaluation of retinal transplants.…”
Section: Tools and Approaches For In Vivo Assessment Of The Transpmentioning
confidence: 99%
“…The canine study demonstrated technical feasibility of film implantation and 5-month functional durability of the implanted films. In the present study, rabbits were used for film implantation since rabbits have been more frequently used as an animal model for ophthalmic surgeries [ 4 ]. In addition, visual evoked potential can be easily recorded in rabbits with thin bony skull, in contrast with difficulty in the recording in dogs with thick bony skull.…”
Section: Discussionmentioning
confidence: 99%
“…no. 80601; Hamilton Company, Inc., Reno, NV, USA), 29 ensuring that all air bubbles have been evacuated from tubing. In both automated and manual injections, the cannula was inserted under the retina followed by the fluid injection.…”
Section: Methodsmentioning
confidence: 99%